(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The blended learning approach was widely implemented across the globe due to the COVID-19 pandemic resulting from the prohibition of face-to-face classes. The blended learning approach existed even before the pandemic. Still, it is now used as the new normal studying system. Learning has been challenging, specifically with learning English grammar. This study aims to identify the effectiveness of using a blended learning approach in learning English grammar on selected grade 12 students at Bestlink College of the Philippines. The researchers used the descriptive method as the research design. Surveys and questionnaires were used to gather data. The researchers also searched for related literature and studies. Random sampling was also used to select the respondents of this study. Based on the answers gathered from the respondents, "having jargon words on online materials." is an aspect that mostly affects the effectivity of learning through online materials. "Applying time management" also makes blended learning effective because the students have been given a chance to organize their time to think and analyze the lessons by scheduling time to answer. Also, "engaging more effort and participation" is a good example of an effect that shows that blended learning has been having positive outcomes because the students use more than one of their skills, like listening, thinking, talking, etc., that made them participate more. Most respondents agreed that "Watching online grammar educational tutorial videos" is an effective strategy for gaining greater knowledge, effective learning and becoming a productive student. Lastly, most respondents agreed with the strategy that advises us to "Practice reading and writing skills." reading and writing skills are a major component of learning English grammar. The researchers concluded that using a blended learning approach in learning English grammar on selected grade 12 students is effective and good. Still, there is always a place for improvement, upgrades and changes that we may apply daily as students. Improving our English vocabulary and literacy may be a big help to be more fluent in speaking, reading and especially understanding English. We need to improve LMS systems and our teaching methods so that learners and teachers will gain knowledge from each other swiftly and effectively.